2009
DOI: 10.1038/ajg.2009.313
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids, IL6 and TNFα Polymorphisms: An Example of Nutrigenetics in Crohn's Disease

Abstract: OBJECTIVES:The aim of this work was to study the interaction between genetic polymorphisms (single-nucleotide polymorphisms, SNPs) of pro-and anti-inflammatory cytokines and fat intake on the risk of developing Crohn's disease (CD) or modifying disease activity. METHODS:Seven SNPs in interleukin 1 (IL1), tumor necrosis factor alpha (TNFα), lymphotoxin alpha (LTα), and IL6 genes were analyzed in 116 controls and 99 patients with CD. The type of fat intake was evaluated, and the interaction between SNPs and diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 30 publications
0
32
2
4
Order By: Relevance
“…Later on, we also observed that a high intake of monounsaturated fat was associated with more active disease. 15 In the present study, although in univariate analysis intake of monounsaturated fat was associated with increased risk of presenting a Z-score lower than À2.0, multivariate analysis did not show that fat intake was an independent risk factor for MBD. Nonetheless, further studies are needed to clarify whether the amount and type of fat intake might influence the prevalence of MBD in patients with CD.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Later on, we also observed that a high intake of monounsaturated fat was associated with more active disease. 15 In the present study, although in univariate analysis intake of monounsaturated fat was associated with increased risk of presenting a Z-score lower than À2.0, multivariate analysis did not show that fat intake was an independent risk factor for MBD. Nonetheless, further studies are needed to clarify whether the amount and type of fat intake might influence the prevalence of MBD in patients with CD.…”
Section: Discussioncontrasting
confidence: 80%
“…In a previous study performed in this same population, we observed that a high intake of total, monounsaturated fat, as well as a higher ratio of n6/n3 polyunsaturated fatty acids, were associated with a more active disease. 15 Fat intake is now regarded as a potent immunomodulatory therapy in patients with CD [30][31][32][33][34][35] either by modulating eicosanoid synthesis, by altering cell membrane fluidity, cell signal transduction, or even gene expression. More interestingly, Gassull et al, 30 in a randomized controlled study performed in patients with active CD, examined the effects of an n-6-versus an n-9-enriched diet as compared with conventional therapy with steroids.…”
Section: Discussionmentioning
confidence: 99%
“…by guest, on May 10, 2018 www.jlr.org Downloaded from plain from the current dataset and are not in line with reports from other disorders that have been associated with elevated immune parameters such as depression ( 19 ) and Crohn's disease ( 48 ). Of note is that in the latter study, the elevated -6: -3 ratio was related to specifi c cytokine genotypes.…”
Section: Discussioncontrasting
confidence: 38%
“…Guerreiro et al (2009) examined the role of the IL-6 À174G/C SNP, fat intake and the risk of developing Crohn's disease. Individuals homozygous for the C allele had a sixfold higher risk for Crohn's disease.…”
Section: Il-6 and Dietary Fasmentioning
confidence: 99%